PROTOCOL: The effects of empowerment‐based nutrition interventions on the nutritional status of women of reproductive age in low‐ and middle‐income countries. Issue 3 (6th July 2021) - Riddle, Alison; Ramage, Abby; Kroeger, Cynthia M.; Bhutta, Zulfiqar A.; Kristjansson, Elizabeth; Taljaard, Monica; Vlassoff, Carol; Wuehler, Sara; Skidmore, Becky; Bennett, Alexandria L.; Rizvi, Anita; Welch, Vivian; et al.
Abstract: The systematic review will answer the follow research questions: (1) What is the effectiveness of different empowerment approaches employed within nutrition interventions on the nutritional status of women of reproductive age in low‐ and middle‐income countries? (2) What implementation and contextual factors contribute to or detract from the effectiveness of these interventions?